STUDI PENAMBAHAN SERAI (Cymbopogon citratus) DAN TEMU MANGGA (Curcuma mangga) TERHADAP KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK MINUMAN SARI UMBI BIT (Beta vulagris L.) - Inten Sharon Datuyanan; Bistok Hasiholan Simanjuntak; Andree Wijaya Setiawan; Yoga Aji Handoko (Faculty of Agricultural Technology, University of Jember, 2020)
As food contains vitamin, mineral and antioxidant, beetroot (Beta vulgaris L.) had beneficial for health. Although beetroot contains a lot of nutritional value, beetroot is less liked by the public because of an earthy taste. For this reason, it needs innovation of the beetroot processing into products that can be accepted by the public, such as beverage fruit drink with food additives. In this study, beetroot juice with food additives, i.e. lemongrass, and turmeric mango was expected to improve taste and acceptable consumer. This study were aimed to analyze the effect of lemongrass and turmeric mango on physicochemical characteristics and determine the organoleptic quality of beetroot juice. This study used a Randomized Block Design (RBD) with the addition of lemongrass and turmeric mango respectively 1%, 3%, 5% concentration in the beetroot juice. Negative control used beetroot juice plain and the positive control used beet juice plus honey. Data were analyzed by variance (ANOVA), if the results obtained were significantly different, the DMRT continuing with 5% significant level. The results showed that the addition of lemongrass and turmeric mango with the concentration of each 1%, 3%, 5% effect on the physicochemical characteristics and organoleptic beet juice. The highest total dissolved solids was 6.92oBrix and the highest betacyanin content of 10.26 mg/L occurred at the addition of 5% turmeric mango. The highest pH value was shown in the negative control (beetroot juice plain) with an average of 6.52. The highest vitamin C content found in the addition of 1% lemongrass about 6.16 mg/100g. The results also showed that the organoleptic beet juice with the addition of 1% lemongrass and the positive control (beet juice plus honey) as a sample that it the most preferred by the panelists. Keywords: beetroot juice, lemongrass, physical-chemistry, organoleptic, turmeric mango